Role of secondary phases and thermal cycling on thermoelectric properties of TiNiSn half-Heusler alloy prepared by different processing routes. (December 2020) - Aversano, Francesco; Palumbo, Mauro; Ferrario, Alberto; Boldrini, Stefano; Fanciulli, Carlo; Baricco, Marcello; Castellero, Alberto
Abstract: Samples of a TiNiSn half-Heusler thermoelectric alloy were prepared using arc melting and rapid solidification by planar flow casting. On the one hand, arc melted samples show multiple phases and need long annealing time to be homogenized into a single phase. On the other hand, rapidly solidified samples show an almost single phase, with a grain refined microstructure. This result is a consequence of the melt undercooling, that allows to bypass the primary solidification of TiNi2Sn full-Heusler and to hinder grain growth. Rapidly solidified samples were consolidated into dense bulk samples by means of open die pressing. The grain refined microstructure obtained by rapid solidification is maintained after sintering, leading to a reduced lattice thermal conductivity, due to a scattering of phonons at grain boundaries. The role of the residual secondary phases (Ni3Sn4, TiNi2Sn and Sn) on the electrical conductivity and thermopower is discussed in the framework of the effective medium theory and related models, explaining the dispersion of thermoelectric properties observed in the literature for nominally stoichiometric TiNiSn. Thermal cycling above 700 K causes surface oxidation, leading to altered thermoelectric properties. Highlights: Rapid solidification inhibits TiNi2 Sn primary phase, refines TiNiSn microstructure. Secondary phases affect thermoelectric properties following effective medium theory. Thermal cycling induces surface oxidation, affecting thermoelectric properties.